Sosialisasi Perpajakan Pada Pelaku Usaha UMKM Di Kota Cimahi - Rizki Indrawan; Annisa Yuniar Larasati; Purwanto; Usman Sastradipraja; Sofia Windarti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities are carried out on MSMEs assisted by the Cimahi city government, West Java. This activity is in the form of socializing the role of MSMEs in taxation and incentives for those affected by COVID-19. The goal is for MSMEs to understand their tax obligations, namely calculating, depositing and reporting taxes and taking advantage of tax incentives provided by the government for business actors affected by the COVID-19 pandemic. Incentives given to MSME actors by reducing the PPh rate (Final Income Tax) to 0.5% of total turnover, according to Government Regulation (PP) Number 23 of 2018 concerning Income Tax on income from businesses received or obtained by Taxpayers who have gross income certain. turnover. Then briefing on the extension of incentives due to this pandemic by utilizing the tax payment abolition facility with the DTP PPh Final mechanism as stated in PMK-82/PMK.03/2021. The implementation is carried out using a webinar mechanism in August 2021. The initial agenda for this activity is coordinated by the activity committee through the WhatsApp group by distributing flyers with the intention that the socialization activities carried out can be followed by the fostered MSME business actors. by the City Government of Cimahi. The output of this activity is to make MSME actors aware of their tax obligations for the business they run, understand how to utilize and use DTP Final Income Tax incentives and calculate, deposit and report taxes.